Integrating testing for sexually transmissible infections into routine primary care for Aboriginal young people: a strengths‐based qualitative analysis. (3rd March 2022) - McCormack, Heather; Guy, Rebecca; Bourne, Christopher; Newman, Christy E.
Abstract: Objectives : This paper examines factors that enabled successful integration of testing for sexually transmissible infections into routine care in Aboriginal Community Controlled Health Services. Methods : This paper reports analysis of qualitative interview data recorded with 19 purposively sampled key informants in New South Wales, Australia, representing six Aboriginal Community Controlled Health Services and five government health bodies supporting those services. The analysis explicitly adopted a strengths‐based approach. Results : Participants reported a strong belief that routine screening overcomes shame and increases engagement with sexual health screening. Incorporating sexual health screening into general medical consultations increases the capture of asymptomatic cases. The Medicare Benefits Schedule 715 Adult Health Check was highlighted as an ideal lever for effective integration into routine care. Conclusion : Integration of testing for sexually transmissible infections into routine care is widely perceived as best practice by senior stakeholders in Aboriginal healthcare in NSW. Findings support continued work to optimise the MBS 715 as a lever to increase testing. Implications for public health : Identifying accessible strategies to increase testing for sexually transmissible infections in Aboriginal Community Controlled Health Services can reduce disparities in notifications affecting Aboriginal young people.